B-alpha /B-beta Ring from Photosynthetic Complex LH4, Modeling of Absorption and Fluorescence Spectra - Heřman, Pavel; Zapletal, David (My University, 2016)
Absorption and steady state fluorescence spectra of B-alpha /B-beta ring from the light-harvesting (LH) pigment-protein complex LH4 are investigated in this contribution. The geometric structure of some LH complexes is known in great detail, e.g. for the LH2 and LH4 complexes from purple bacteria. The properties of such complexes are strongly influenced by their interactions with environment. These interactions could be modeled by static and dynamic disorder. Different types of static disorder are considered and discussed. Resulting spectral profiles within full Hamiltonian model are presented and compared with our previous results within the nearest neighbour approximation model. Distribution of the quantity P(alpha) d(alpha)^2 that appears in the expression for steady state fluorescence spectrum is also studied. Comparison of the results for B-alpha /B-beta ring from LH4 complex and B850 ring from LH2 complex is also done.
Prstenec B-alfa /B-beta z fotosyntetického komplexu LH4, modelování absorpčních a fluorescenčních spekter
Keywords: LH4; LH2; absorption and fluorescence spectrum; static and dynamic disorder; LH4; LH2; absorpční a fluorescenční spektrum; statický a dynamický nepořádek